Analisis Yuridis Penerapan Pasal 74 Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas Terhadap Pelanggaran CSR - Dewinda Ari Fitriyani; Fany Aprillia Regita Cahyani; Sumriyah Sumriyah (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The implementation of Corporate Social Responsibility is carried out as a form of corporate social responsibility. Corporate Social Responsibility is very important to be carried out by companies, especially companies whose operational activities have an impact on the community's environment and the environment around the company. The Government of Indonesia in implementing Corporate Social Responsibility has regulated it in Law Number 40 of 2007 concerning Limited Liability Companies, there are several articles that regulate the provisions of corporate social responsibility obligations, but there are still companies that do not comply with these social responsibility obligations and commit violations of Corporate Social Responsibility. One of the companies that committed CSR violations was PT. Freeport Indonesia to the Amuge and Comorian communities in Timika, Papua. The purpose of this study is to understand the application of article 74 of Law Number 3 of 2007 concerning Limited Liability Companies to the form of corporate responsibility to the community and find out the legal sanctions for companies that violate corporate social responsibility obligations. The type of legal research used in this study is normative legal research. Legal sources used are sourced from primary and secondary legal materials obtained from literature studies